Production of citric acid from sewage treatment plant (STP) through liquid state bioconversion - Nur Hanis Mohamad Hanapi (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The application of sewage sludge as main substrate for the production of citric acid is still new and can be considered as rare in this field of bioconversion. Citric acid mostly is produced from agricultural wastes such as sugarcane bagasse, empty fruit bunches, cane molasses, cassava bagasse, sugar whey, cheese whey, brewery waste and many more. Thus the study for the production of citric acid from sewage treatment plant (STP) sludge through liquid state bioconversion by local isolate Aspergillus niger 0103A was accomplished by several studies. It was conducted based on the main objective of this study which is to produce citric acid from sewage treatment plant sludge by Aspergillus niger. In order to accomplish the main objective, few subsequent studies have been performed. In the selection and determination of fermentation major substrate, three different media which are sewage sludge, palm oil mill effluent (POME) and mineral solution containing essential trace elements for microorganism growth have been screened. The ability of the fermentation media to produce citric acid in higher yield is observed. From the investigation it is concluded that sewage sludge was the most potential substrate to produce maximum amount of citric acid by Aspergillus niger with the addition of co-substrate which was sucrose (commercial sugar). The study continued with the screening experiment for potential local isolates of Aspergillus niger in producing maximum quantity of citric acid. In this screening experiment nineteen local isolates of Aspergillus niger were screened using sewage sludge as the fermentation media. It is observed that Aspergillus niger 0103A gave the highest production of citric acid (20.80 g/1). Media optimization was carried out using Plackett-Burman design of experiment. Eleven media compositions were designed as to investigate and determine the most suitable composition for maximum citric acid production. These factors are selected for media screening which are empty fruit bunch (EFB), rice straw (RS), yeast extract (YE), urea, sucrose (commercial sugar), cassava flour, sewage sludge total suspended solids (TSS) composition, methanol, mineral (Mg, Mn, Zn, Cu), KH2P04, and NH.iN03. There were twelve experiments conducted. The highest production of citric acid obtained was 20.9 g/1 while the lowest was 0.60 g/1. From the result it was observed that few factors affected the production of citric acid. They were sewage sludge total suspended solids (TSS) composition, cassava, sucrose (commercial sugar), methanol, KH2P04 and urea. Faced centred central composite design (FCCCD) was used for the selected two factors in this study which were sewage sludge and sugar. It is observed that highest citric acid obtained was 28.26 g/1, which was at TSS 0. 7% of sewage sludge and 8% (w/v) of sugar content in the fermentation media. However, 5% sugar gave better yield compared to 7% sugar in higher citric acid production, thus making 5% sugar concentration as co-substrate in process optimization. Three parameters were experimented in the optimization of process condition, which are pH, agitation and aeration. Fractional factorial design is used for the optimization process and resulted with 23.68 g/1 of citric acid produced. It is observed that both factors; pH and aeration had major effects in citric acid production compared to agitation in the fermentation process.